1953
DOI: 10.1128/jb.66.5.568-571.1953
|View full text |Cite
|
Sign up to set email alerts
|

THE INFLUENCE OF VARIOUS METABOLITES UPON THE p -AMINOBENZOATE-PANTOTHENATE INTERACTION IN BACTERIUM LINENS

Abstract: The nutritional equivalence of pantothenate and p-aminobenzoate for the growth of Bacterium linens and the reversal of growth inhibition by sulfanilamide and salicylate has indicated a biochemical relationship between pantothenate and p-aminobenzoate (Purko et al., 1953). Recently, Pomper (1952) observed that the pantothenate, as well as the methionine, histidine, and adenine requirements of a mutant of Saccharomyces cerevisiae, could be replaced by high p-aminobenzoate concentrations and also has

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1954
1954
2004
2004

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…35 This activity was stimulated by the addition of divalent metal ions and to some extent by the addition of tetrahydrofolate. This finding was supported by earlier data that p-aminobenzoic acid (PABA) was involved in pantothenate metabolism [36][37][38] and suggested a mechanism analogous to that reported for serine hydroxymethyltransferase. 39 The enzyme was purified to a greater level of homogeneity by Teller et al 40 and this purified enzyme preparation was found to be dependent on 5,10-methylenetetrahydrofolate.…”
Section: The Initial Precursorsupporting
confidence: 83%
“…35 This activity was stimulated by the addition of divalent metal ions and to some extent by the addition of tetrahydrofolate. This finding was supported by earlier data that p-aminobenzoic acid (PABA) was involved in pantothenate metabolism [36][37][38] and suggested a mechanism analogous to that reported for serine hydroxymethyltransferase. 39 The enzyme was purified to a greater level of homogeneity by Teller et al 40 and this purified enzyme preparation was found to be dependent on 5,10-methylenetetrahydrofolate.…”
Section: The Initial Precursorsupporting
confidence: 83%